The kindness of God: metaphor, gender, and religious language - Soskice, Janet Martin (Oxford University Press, 2007)
Fathers, sons, brothers, kings. Does the predominantly masculine symbolism of the Biblical writings exclude women or overlook the riches of their spiritual life? Janet Martin Soskice opens up the Bible's imagery for sex, gender, and kingship, by discussing its place in the central teachings of Christian theology. - ;Fathers, sons, brothers, kings. Does the predominantly masculine symbolism of the Biblical writings exclude women or overlook the riches of their spiritual life? If Christ is 'the second Adam' and the one on whom all Christian life must be patterned, then what about Eve? This book